2017
DOI: 10.1920/wp.cem.2017.1417
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric instrumental variable estimation under monotonicity

Abstract: The ill-posedness of the nonparametric instrumental variable (NPIV) model leads to estimators that may suffer from poor statistical performance. In this paper, we explore the possibility of imposing shape restrictions to improve the performance of the NPIV estimators. We assume that the function to be estimated is monotone and consider a sieve estimator that enforces this monotonicity constraint. We define a constrained measure of ill-posedness that is relevant for the constrained estimator and show that, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Finally, monotonicity of the relationship between the outcome and the explanatory variable is a weak assumption that is often directly implied by economic theory, for example, when the conditional mean E ( Y | X = x ) is a production, cost, or utility function. Examples can be found in Matzkin (1994); Olley and Pakes (1996); Cunha, Heckman, and Schennach (2010); Blundell, Horowitz, and Parey (2012, 2017); Kasy (2014); Wilhelm (2015); Hoderlein et al (2015); and Chetverikov and Wilhelm (2017), among many others.…”
Section: Nonparametric Model—the New Dgmtest Commandmentioning
confidence: 99%
“…Finally, monotonicity of the relationship between the outcome and the explanatory variable is a weak assumption that is often directly implied by economic theory, for example, when the conditional mean E ( Y | X = x ) is a production, cost, or utility function. Examples can be found in Matzkin (1994); Olley and Pakes (1996); Cunha, Heckman, and Schennach (2010); Blundell, Horowitz, and Parey (2012, 2017); Kasy (2014); Wilhelm (2015); Hoderlein et al (2015); and Chetverikov and Wilhelm (2017), among many others.…”
Section: Nonparametric Model—the New Dgmtest Commandmentioning
confidence: 99%
“…Shape restrictions can greatly help inference in this model. Chetverikov and Wilhelm () showed that monotonicity can improve rates of convergence. If the model is partially identified, shape restrictions can also dramatically reduce the identified set.…”
Section: Setup and Examplesmentioning
confidence: 99%
“…Other recent work in this area includes Chetverikov (), Chetverikov and Wilhelm (), Fang and Seo (), Freyberger and Horowitz (), Freyberger and Reeves (), Gutknecht (), and Horowitz and Lee (). All of these papers focus on nonparametric regression or nonparametric IV regression models, except Fang and Seo () and Freyberger and Reeves (), which consider general setups but require point identification.…”
Section: Introductionmentioning
confidence: 99%
“…when E P [µ(Y )|X * = x * ] is a production, cost, or utility function. Examples can be found in Matzkin (1994), Olley and Pakes (1996), Cunha, Heckman, and Schennach (2010), Parey (2012, 2016), Kasy (2014), Wilhelm (2015), Hoderlein, Holzmann, Kasy, and Meister (2016), Chetverikov and Wilhelm (2017), among many others.…”
Section: Equivalencementioning
confidence: 99%